Optimized Photoactivatable Lipid Nanoparticles Enable Red Light Triggered Drug Release. Issue 21 (20th April 2021) - Chander, Nisha; Morstein, Johannes; Bolten, Jan S.; Shemet, Andrej; Cullis, Pieter R.; Trauner, Dirk; Witzigmann, Dominik
Abstract: Encapsulation of small molecule drugs in long‐circulating lipid nanoparticles (LNPs) can reduce toxic side effects and enhance accumulation at tumor sites. A fundamental problem, however, is the slow release of encapsulated drugs from these liposomal systems at the disease site resulting in limited therapeutic benefit. Methods to trigger release at specific sites are highly warranted. Here, it is demonstrated that incorporation of ultraviolet (UV‐A) or red‐light photoswitchable‐phosphatidylcholine analogs (AzoPC and redAzoPC) in conventional LNPs generates photoactivatable LNPs (paLNPs) having comparable structural integrity, drug loading capacity, and size distribution to the parent DSPC‐cholesterol liposomes. It is shown that 65–70% drug release (doxorubicin) can be induced from these systems by irradiation with pulsed light based on trans ‐to‐ cis azobenzene isomerization. In vitro it is confirmed that paLNPs are non‐toxic in the dark but convey cytotoxicity upon irradiation in a human cancer cell line. In vivo studies in zebrafish embryos demonstrate prolonged blood circulation and extravasation of paLNPs comparable to clinically approved formulations, with enhanced drug release following irradiation with pulsed light. Conclusively, paLNPs closely mimic the properties of clinically approved LNPs with the added benefit of light‐induced drug release making them promising candidates for clinical development. Abstract : Incorporating photoswitchable‐phosphatidylcholine into conventional lipid nanoparticles (LNPs) generates photoactivatable LNPs (paLNPs). In vitro it is shown that upon irradiation, 70% drug is released which induces cytotoxic effects in human cancer cells. In vivo studies in zebrafish embryos confirm that paLNPs have similar pharmacokinetic properties as the clinically approved LNPs with added benefits of light‐induced drug release based on trans ‐to‐ cis azobenzene isomerization.